Simulasi FEM dan Validasi Struktur Mikro terhadap Pengaruh Kecepatan Pengelasan SMAW pada ASTM A36 - Amelia Maureta, Yola; Windyandari, Aulia (Journal of Applied Mechanical Technology, 2025)
ABSTRACT – Welding is one of the metal joining processes commonly used in the shipping industry, but this process has the potential to cause residual stress and distortion due to uneven heat distribution. This study aims to analyze the effect of welding speed variations on residual stress and distortion in ASTM A36 plate butt joints using the SMAW (Shielded Metal Arc Welding) welding method. The method used in this study is a numerical simulation based on the Finite Element Method (FEM) using ANSYS 2024 R2 software, with welding speed variations of 15 cm/min, 20 cm/min, and 25 cm/min. Validation was carried out through microstructure tests on welding specimens using a metallographic microscope. The simulation results show that the higher the welding speed, the lower the residual stress and distortion values. A speed of 25 cm/min gives the best results with a residual stress of 160,29 MPa and a distortion of 0,1436 mm. The results of the microstructure test in the weld area and HAZ show fine and even grains, supporting the simulation results that high welding speeds produce lower heat input and more stable microstructures. Thus, a welding speed of 25 cm/min is recommended as the optimal parameter in minimizing residual stress and distortion in ASTM A36 plates.